Tailoring the shell structures in core-shell metal nanostructures for improved catalytic reduction of nitroaromatics - Manickam Sundarapandi; Alagarsamy Pandikumar; Perumal Rameshkumar; Ramasamy Ramaraj (Nano Trends)
Core-shell metal nanostructures have garnered significant attention from researchers worldwide in recent years due to their size- and shape-dependent properties, which arise from the synergistic effects between the core and shell. These properties are particularly valuable for applications in catalysis. This review focuses on recent advancements in the synthesis of various metal shell layers on cores of different sizes and shapes for the catalytic reduction of nitroaromatics. Initially, recent contributions to the synthesis of diverse bimetallic nanostructures, including hollow, crown-jewel, alloy, and core-shell architectures are summarized. Subsequently, the influence of tailoring metal shells, including monolayer, bilayer, and alloy layer metal shells on core metals, on the catalytic activity of nitroaromatics is discussed. This review highlights significant progress in the design and synthesis of various nanostructures and compositions through precise control of nucleation and growth processes using specific synthetic methods. Moreover, the discussion focused on how the catalytic reduction of nitroaromatics is influenced by the synergistic effect when different layers of metal shells are applied to the core. Furthermore, the advantages and limitations associated with the synthesis of core-shell nanostructures are highlighted in each section. Finally, perspectives on future research directions for core-shell metal nanostructures are provided.